Management, Husbandry and Milk Production in Dairy Farms in Khartoum State (Journal of Veterinary Medicine and Animal Production, 2022)
This study was designed to assess current situation of dairy farms in Khartoum State – Eastern Nile area. Sixty dairy farms were selected randomly and the owners were directly interviewed using structural questionnaire during the period of March to June 2010. High significant (P
Keywords: Husbandry and Milk